Effects of bisphenol A exposure on DNA integrity and protamination of mouse spermatozoa. (5th September 2019) - Pan, D.; Feng, D.; Ding, H.; Zheng, X.; Ma, Z.; Yang, B.; Xie, M.
Abstract: Background: Bisphenol A is widely used in the manufacture of polycarbonate plastics and has caused increasing concern over its potential adverse impacts on spermatogenesis. However, the effect of bisphenol A on spermiogenesis is yet to be explored. Objectives: To evaluate whether bisphenol A has adverse effects on DNA integrity and protamination of spermatogenic cell. Materials and methods: Newborn male mice were subcutaneously injected with bisphenol A (0.1, 5 mg/kg body weight, n  = 15) or coin oil (control group, n  = 20) daily from post‐natal day 1 until 35. At post‐natal day 70, epididymis caudal spermatozoa and testes were collected. Sperm count, sperm motility, and sperm morphology were analyzed. The sperm chromatin structure assay was performed to examine the sperm DNA fragmentation. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) method was used to assess apoptosis of spermatogenic cells. The ultrastructural features of testicular sections were examined under a transmission electron microscope. Western blot and RT‐PCR were used to detect the expression levels of transition protein (Tnp) 1 and Tnp2, protamine (Prm) 1 and Prm2 protein, and mRNA in mice testes. Results: Bisphenol A significantly reduced sperm counts, impaired sperm motility, and increased the percentage of malformed spermatozoa. Poor sperm chromatin integrity and increased TUNEL‐positive spermatogenic cells were also observed in mice exposed to bisphenol A. Ultrastructural analysis of testes showed that bisphenol A exposure caused incomplete chromatin condensation, retention of residual cytoplasm, and abnormal acrosome formation. In addition, the relative expression levels of Tnp2 and Prm2 in mice testes decreased significantly in bisphenol A groups. Discussion and conclusion: Our findings identified that neonatal bisphenol A exposure may negatively contribute to the sperm quality in adult mice. Mechanistically, we showed that bisphenol A reduced sperm chromatin integrity along with increased DNA damage, which may be due to poor protamination of spermatozoa.